Immunohistochemical localization of short chain cartilage collagen (type X) in avian tissues (The Rockefeller University Press, 1985)
Monoclonal antibodies were produced against the recently described short chain cartilage collagen (type X collagen), and one (AC9) was extensively characterized and used for immunohistochemical localization studies on chick tissues. By competition enzyme-linked immunosorbent assay, antibody AC9 was observed to bind to an epitope within the helical domain of type X collagen and did not react with the other collagen types tested, including the minor cartilage collagens 1 alpha, 2 alpha, 3 alpha, and HMW-LMW. Indirect immunofluorescence analyses with this antibody were performed on unfixed cryostat sections from various skeletal and nonskeletal tissues. Only those of skeletal origin showed detectable reactivity. Within the cartilage portion of the 13-d- old embryonic tibiotarsus (a developing long bone) fluorescence was observed only in that region of the diaphysis containing hypertrophic chondrocytes. None was detectable in adjacent regions or in the epiphysis. Slight fluorescence was also present within the surrounding sleeve of periosteal bone. Consistent with these results, the antibody did not react with the cartilages of the trachea and sclera, which do not undergo hypertrophy during the stages examined. It did, however, lightly react with the parietal bones of the head, which form by intramembranous ossification. These results are consistent with our earlier biochemical analyses, which showed type X collagen to be a product of that subpopulation of chondrocytes that have undergone hypertrophy. In addition, either it or an immunologically cross- reactive molecule is also present in bone, and exhibits a diminished fluorescent intensity as compared with hypertrophic cartilage.